Language and power [ a resource book for students - Simpson, Paul , 1959-; Mayr, Andrea , 1972- (Routledge English language introductions, 2010)
Routledge English Language Introductions cover core areas of language study and are one-stop resources for students. Assuming no prior knowledge, books in the series offer an accessible overview of the subject, with activities, study questions, sample analyses, commentaries and key readings - all in the same volume. The innovative and flexible 'two-dimensional' structure is built around four sections - introduction, development, exploration and extension - which offer self-contained stages for study. Each topic can also be read across these sections, enabling the reader to build gradually on t.